The PR professional's handbook : powerful, practical communications - Black, Caroline, 1956- (2014)
"At a time when rapid changes in communications technology are having a major impact on the way businesses choose to communicate, more people are having to understand the principles of modern PR and how they can underpin effective business management. Whether as a student (undergraduate or as part of ongoing professional development), consultant or business owner, there are areas of good PR practice that must be followed, while at the same time new channels of communication - notably social media - are creating fresh challenges and opportunities. The PR Professional's Handbook offers practical advice and solutions for anyone involved in the PR function, as well as a full breakdown on the individual skills required in briefing, writing and presenting. The book covers the role and importance of PR and communications in organisations, key theories for PR, skills and disciplines, channels and creativity"--
"Rapid changes in technology are having a major impact on the way businesses choose to reach their audience. As a result, an increasing number of people need a better understanding of modern PR and how its principles can underpin effective business management. Keeping track of the best PR practices, as well as the new communications channels that arise can be overwhelming for professionals new to the PR function.With practical advice and solutions, The PR Professional's Handbook is a complete introductory text that provides a full breakdown of the skills required in communications, including briefing, listening, questioning, writing, selling and presenting. Highlighting international case studies throughout the text, Black offers a fresh interpretation of the basics, combined with the latest information on technology and social media. "--
Machine generated contents note: Foreword -- Conrad Bird - Director of Communications, Cabinet Office, British Government -- Introduction -- Chapter 1 The role and importance of communications in organisations -- Chapter 2 Key theories for communicators -- Chapter 3 The communications professional -- Chapter 4 Planning communications programmes and campaigns -- Chapter 5 Communications and related disciplines -- Chapter 6 Understanding audiences - the psychology of communications -- Chapter 7 Using the right channels for communications -- Chapter 8 Creativity in communications development -- Chapter 9 Visual imagery in communications -- Chapter 10 Communications skills essentials.
Includes bibliographical references (pages 355-359) and index.
Keywords: Business communication -- Handbooks, manuals, etc; Communication in organizations -- Handbooks, manuals, etc; Public relations -- Handbooks, manuals, etc; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Public Relations; Print books